Implementation of Science Story Media Etnosains Based to Boost Students Concept and Scientific Attitudes - Rahma Rahma; Nanda Safarati (Jurnal Pembelajaran Fisika, 2020)
This research aims to produce an ethnics-based science story media to foster understanding of scientific concepts and attitudes, especially on a material equilibrium of rigid bodies. This type of research is one group pretest and posttest design. The results of this study indicate that the N-gain understanding of concepts in the experimental class (g = 0.69) is higher than the control class (g = 0.08), as well as the results of the analysis of scientific attitudes of students in the experimental class (g = 0.73) higher than the control class (g = 0.08). Also, there was a significant difference in the average test results of students' understanding of concepts and scientific attitudes (p <0.05) between the experimental class and the control class. The conclusion is the use of ethnics-based science story media can improve students' understanding of scientific concepts and attitudes.Keywords: ethnics, scientific attitude, science story, understanding of concepts   DOI: http://dx.doi.org/10.23960/jpf.v8.n1.202005